1995
DOI: 10.3109/00365519509104975
|View full text |Cite
|
Sign up to set email alerts
|

Acute alveolar hypoxia increases endothelin-1 release but decreases release of calcitonin generelated peptide in isolated perfused rat lungs

Abstract: The release and vascular effects of calcitonin gene-related peptide (CGRP) and endothelin-1 (ET-1) during acute alveolar hypoxia (O2 2%) were examined in isolated blood-perfused rat lungs. In 10 lungs, repeatedly ventilated with hypoxic gas for 5 min, samples from effluent blood were taken during hypoxia and analysed for plasma levels of CGRP-like immunoreactivity (-LI) and ET-1-LI. The plasma levels of ET-1-LI were significantly (p < 0.05) increased in hypoxic lungs (5.5 +/- 0.5 pmol l-1) compared with normox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
1
10
1
1
Order By: Relevance
“…In some studies (419, 1180, 1250, 1508), hypoxia did not increase pulmonary ET-1 production. In others (288, 767,1175,1883), both induction of ET-1 production by hypoxia and reversal of pulmonary vasoconstriction induced by ET-1 occurred very slowly, whereas the onset and offset of HPV occur rapidly (see sect. IIA2).…”
Section: I) Endothelin-1mentioning
confidence: 94%
See 1 more Smart Citation
“…In some studies (419, 1180, 1250, 1508), hypoxia did not increase pulmonary ET-1 production. In others (288, 767,1175,1883), both induction of ET-1 production by hypoxia and reversal of pulmonary vasoconstriction induced by ET-1 occurred very slowly, whereas the onset and offset of HPV occur rapidly (see sect. IIA2).…”
Section: I) Endothelin-1mentioning
confidence: 94%
“…Adenosine-activated potassium current in smooth muscle cells isolated from the pig coronary artery. J Physiol 471:[767][768][769][770][771][772][773][774][775][776][777][778][779][780][781][782][783][784][785][786]1993.364. Daut J, Maier-Rudolph W, von Beckerath N, Mehrke G, Gunther K, Goedel-Meinen L. Hypoxic dilation of coronary arteries is mediated by ATP-sensitive potassium channels.…”
mentioning
confidence: 99%
“…CGRP has one endothelium-dependent mode of action (6) and also dilates some systemic arteries and the pulmonary circulation, inde-pendent of endothelial factors such as nitric oxide (27,35). Our laboratory previously shown that endogenous CGRP has an essential protective role in hypoxiainduced PH (HPH) (37,38) and that circulating levels of immunoreactive CGRP are reduced in rats with HPH, thus allowing constrictors such as endothelin (ET)-1 to act unopposed (14,39). Vasoconstriction is further enhanced by increased ET-1 synthesis in hypoxia (24).…”
mentioning
confidence: 99%
“…Helset et al. () found increased ET‐1 protein levels in the perfusate of isolated rat lungs even earlier, that is after 5 min exposure to FiO 2 0.02. FiO 2 0.21 in our study was not sufficient to maintain adequate oxygen saturation over 120 min of ventilation (SpO 2 ~78% after 120 min).…”
Section: Discussionmentioning
confidence: 98%